Adnexal torsion in a 20-year-old nulliparous woman - Gurung, Kismat; Adhikari, Pritha (Journal of Gandaki Medical College-Nepal, 2024)
Twisting of an organ or a part of it along its own axis is known as torsion. Twisting of the ovary, often along with the fallopian tube is known as adnexal torsion. Both the ovaries and fallopian tubes are often involved so the preferred term is adnexal torsion rather than ovarian torsion. It is the fifth most common gynaecological emergency. Twisting of the ovary, often along with the fallopian tube on its ligamentous supports results in vascular compromise and infarction of the ovary. The patient usually presents with a sudden onset of intense pain; however, this is not always the case. Imaging plays a vital role in the diagnosis of adnexal torsion and the definitive management of surgical detorsion which facilitates preservation of the ovary.